Finite-time stochastic input-to-state stability and observer-based controller design for singular nonlinear systems - Zhao, Feng; Chen, Xiangyong; Cao, Jinde; Guo, Ming; Qiu, Jianlong (Nonlinear Analysis: Modelling and Control, 2020)
This paper investigated observer-based controller for a class of singular nonlinear systems with state and exogenous disturbance-dependent noise. A new sufficient condition for finite-time stochastic input-to-state stability (FTSISS) of stochastic nonlinear systems is developed. Based on the sufficient condition, a sufficient condition on impulse-free and FTSISS for corresponding closed-loop error systems is provided. A linear matrix inequality condition, which can calculate the gains of the observer and state-feedback controller, is developed. Finally, two simulation examples are employed to demonstrate the effectiveness of the proposed approaches.